Clinical spectrum of ear, nose and throat foreign bodies in North Western Nigeria - Adedeji, Taiwo Olugbemiga (Afr Health Sci, 2016)
BACKGROUND: Ear, nose and throat foreign bodies (FBs) are common occurrences particularly among children. This study reviewed the clinical spectrum of ENT FBs, their treatment and outcomes as seen in a tertiary health center in North Western Nigeria. METHOD: The study was a retrospective chart review of patients that were managed for FB impaction in a tertiary health institution in North Western Nigeria over a four year period. RESULT: There were 239 patients; M: F: 1.2:1. Majority of FB impaction (46.4%) occurred in children. Majority (68.7%) were otic and FBs. 18.0% of the patients had had failed attempted removal by non ENT specialists. About 25% of these patients developed complications. Majority (62.0%) of these complications occurred in the hand of non-ENT medical personnel. CONCLUSION: Ear, nose and throat foreign bodies are common in North-Western Nigeria with the highest incidence in children. Removal attempts by untrained health professionals and lack of experience in FB management predisposes to complications. Parental education on close monitoring of their children to avoid such incidences and the need to immediately seek an Otorhinolaryngologist to prevent complications are emphasized.